The plasminogen receptor Plg‐RKT regulates adipose function and metabolic homeostasis. (21st December 2021) - Samad, Fahumiya; Bai, Hongdong; Baik, Nagyung; Haider, Patrick; Zhang, Yuqing; Rega‐Kaun, Gersina; Kaun, Christoph; Prager, Manfred; Wojta, Johann; Bui, Quyen; Chakrabarty, Sagarika; Wang, Jing; et al.
Abstract: Background: Plg‐RKT, a unique transmembrane plasminogen receptor, enhances the activation of plasminogen to plasmin, and localizes the proteolytic activity of plasmin on the cell surface. Objectives: We investigated the role of Plg‐RKT in adipose function, metabolic homeostasis, and obesity. Methods: We used adipose tissue (AT) sections from bariatric surgery patients and from high fat diet (HFD)‐induced obese mice together with immunofluorescence and real‐time polymerase chain reaction to study adipose expression of Plg‐RKT . Mice genetically deficient in Plg‐RKT and littermate controls fed a HFD or control low fat diet (LFD) were used to determine the role of Plg‐RKT in insulin resistance, glucose tolerance, type 2 diabetes, and associated mechanisms including adipose inflammation, fibrosis, and ectopic lipid storage. The role of Plg‐RKT in adipogenesis was determined using 3T3‐L1 preadipocytes and primary cultures established from Plg‐RKT –deficient and littermate control mice. Results: Plg‐RKT was highly expressed in both human and mouse AT, and its levels dramatically increased during adipogenesis. Plg‐RKT –deficient mice, when fed a HFD, gained more weight, developed more hepatic steatosis, and were more insulin resistant/glucose intolerant than HFD‐fed wild‐type littermates. Mechanistically, these metabolic defects were linked with increased AT inflammation, AT macrophage and T‐cell accumulation, adipose and hepatic fibrosis, and decreased insulin signaling in the AT and liver. Moreover, Plg‐RKT regulated the expression of PPARγ and other adipogenic molecules, suggesting a novel role for Plg‐RKT in the adipogenic program. Conclusions: Plg‐RKT coordinately regulates multiple aspects of adipose function that are important to maintain efficient metabolic homeostasis.